Polymer and Composition Materials - Salim Madrahimovich Otajonov; Qaxxorova Barchinoy Abdiraximovna (Zien Journals, 2022)
In order to create an existing stock of construction materials, firstly, it is necessary to use them sparingly, to increase the impact of the structure on the properties, and secondly, to find new types of raw materials and produce construction materials based on them. The most important of these materials are plastics, rubbers, cellulose-based materials, ceramics and composite materials. Composite materials based on metal, polymer and ceramic are the materials that will determine the future development of the technique. At present, these materials are helping to solve important technical problems. The need for them is growing. This article provides information about non-metallic materials, polymer materials, synthetic polymers, composite materials, polymer composite materials, their properties, properties, textolites
Keywords: polymer; properties; technical; composite